BUDAYA BAHARI DAM TRADISI NELAYAN DI INDONESIA - Yunandar, Yunandar (Sabda: Jurnal Kajian Kebudayaan, 2006)
There are at least five phenomena which mark the complexity of maritime culture and fisherman tradition in Indonesia; social group of the maritime society, the development of economic sectors concerning sea products, social hierarchy in the daily maritime activities, the relationship between the elements of maritime culture and life sectors of the society, and the continuation and alteration of maritime culture's elements. In order to acquire a deep study on the complexity of maritime culture, there are several concepts used in this paper: Koentjaraningrat's concept of "three forms of culture", Sanjek's concept of "the dynamic culture and creation", and Vadya's concept of "contextual progressive explanatory method". The forms of maritime culture include the system of culture, belief, institution, and production technology. Meanwhile, the dynamics of maritime culture and fisherman tradition is determined not only by the internal factors but also the external forces, such as, innovation on technology, government policy, university interventions, nongovernmental organizations, donor institution, and regional, national, and even global market. Apparently, those external forces have brought negative impacts on the life of maritime society, marked by the decrease of economic prosperity, natural resources and sea environment. The negative impacts can be avoided by applying community-based management in the development of maritime culture